Two faces of power: cohesion and power groups in two democratic governments - Villena-Oliver, Andrés (My University, 2014)
Study of the internal relational structure of two democratic governments in its initial configuration after general elections.
Esta comunicación presenta algunos resultados de la investigación realizada por el autor para su tesis doctoral.
Keywords: Elites; Poder (Ciencias sociales); Political power; Elites; Social network analysis